MANAJEMEN SISTEM KEARSIPAN DI UPT METEOROLOGI KELAS 1 SULTAN AJI MUHAMMAD SULAIMAN - Minarto, Eko Bambang; Malik, Asep; Mardiyanti, Erika; Yulianti, Mangisi Sumihar (Jurnal Widya Climago, 2023)
The management of the archive system at the Meteorological Station Class I Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan is still not optimal both in terms of infrastructure and human resources. For that reason, it is necessary to create an archiving system management that is able to improve more optimal archiving. The purpose of this change action is to improve the management of the archival system at the Meteorological Station Class I Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan so as to improve better performance, expedite activities and the archival value of the Meteorological Station Class I Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan can increase